On wilsonian flows in gauge theories - Pawlowski, Jan M. (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2001)
An Exact Renormalisation Group (ERG) approach to non-Abelian gauge theories is discussed. We focus on the derivation of universal beta-functions and the choice of the initial effective action, the latter being a key input in the approach. To that end we establish the map between Gell-Mann-Low scaling of the full theory and the scaling in an ERG approach. Then this map is used to derive the 2-loop β-function within a simple straightforward calculation. The implications for the choice of the initial effective action are discussed.
Gesehen am 06.12.2017